Adiabatic phase-conserving processes for executing quantum operations with ultracold atoms. (June 2017) - Beterov, I.I.; Tret'yakov, D.B.; Entin, V.M.; Yakshina, E.A.; Khamzina, G.N.; Ryabtsev, I.I.
Abstract: We have studied the regimes of deterministic single-atom Rydberg excitation in the conditions of Rydberg blockade and the methods of compensation for the dynamic phase of the wave function during the adiabatic passage. Using these methods, we have proposed schemes of single-qubit and two-qubit quantum states with mesoscopic atomic ensembles containing a random number of atoms, considred as quibits. The double adiabatic passage of the Förster resonance for two interacting atoms with a deterministic phase shift can be used for the implementation of two-qubit gates with reduced sensitivity of the gate fidelity to the fluctuations of the interatomic distance.